2022
DOI: 10.1186/s13018-022-03411-y
|View full text |Cite
|
Sign up to set email alerts
|

Superior capsule reconstruction, partial cuff repair, graft interposition, arthroscopic debridement or balloon spacers for large and massive irreparable rotator cuff tears: a systematic review and meta-analysis

Abstract: Background Multiple non-arthroplasty surgical techniques are described for the management of large and massive irreparable rotator cuff tears. There is currently no consensus on the best management strategy. Our aim was to compare clinical outcomes following arthroscopic debridement, arthroscopic partial cuff repair, superior capsule reconstruction, balloon spacers or graft interposition for the management of large and massive irreparable rotator cuff tears. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 106 publications
1
9
0
Order By: Relevance
“…It has been widely confirmed in the literature that attempting to repair as much as possible of the cuff, converting it into a functional rotator cuff tear by recreating a balanced forced couple, can be helpful in reducing pain, as well as improving functional outcomes [7,9]. However, despite the improved functional outcomes, partial repair of the cuff often leads to not negligible retear rates [7] and glenohumeral alterations at the midterm follow-up [20]. More severe scenarios, such as external rotation with the arm at the side + external rotation at 90°of abduction lag (infraspinatus and teres minor complete dysfunction) without pseudoparalysis, need additional considerations.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely confirmed in the literature that attempting to repair as much as possible of the cuff, converting it into a functional rotator cuff tear by recreating a balanced forced couple, can be helpful in reducing pain, as well as improving functional outcomes [7,9]. However, despite the improved functional outcomes, partial repair of the cuff often leads to not negligible retear rates [7] and glenohumeral alterations at the midterm follow-up [20]. More severe scenarios, such as external rotation with the arm at the side + external rotation at 90°of abduction lag (infraspinatus and teres minor complete dysfunction) without pseudoparalysis, need additional considerations.…”
Section: Discussionmentioning
confidence: 99%
“…However, at the 2-year mark post-surgery, the groups undergoing balloon spacers, arthroscopic debridement, and partial cuff repair exhibited unfavorable outcomes in shoulder scores. Additionally, high rates of retear were reported in partial cuff repairs (45%), and superior capsule reconstruction (21%) [ 28 ]. Therefore, methods aimed at reducing tension, such as footprint medialization repair, have been reported to decrease retear rates [ 9 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a wide range of radiographic findings for intact bridging rotator cuff grafts. 8 Aggregate reporting on SCR have detailed satisfactory improvement in clinical outcomes 7 and variable rates of reoperation with the most common being revision to RSA. 22 Notably, recent analysis has suggested that a superior capsule graft may not need to demonstrate radiographic healing to yield the intended effect of mechanical impedance to superior translation of the humerus.…”
Section: Discussionmentioning
confidence: 99%
“…This may reduce the risk of graft failure that has been reported for single graft reconstruction. 7 , 12 …”
Section: Discussionmentioning
confidence: 99%